The utility of molecular diagnostics in tumour surveillance in Beckwith-Wiedemann syndrome – clinical genetics point of view in light of a case report - Drankowska, Justyna; Kos, Michał; Kościuk, Andrzej; Nurzyńska-Flak, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Beckwith-Wiedemann syndrome (BWS) is the most frequent congenital overgrowth syndrome. Its clinical features are variable, including macrosomia, hemihyperplasia, and macroglossia. The most important feature appears to be the increased risk of embryonal tumours, depending on the molecular aetiology of BWS. The underlying molecular abnormalities might be genetic or epigenetic, and they involve the segment of the genome – chromosome 11p15. The aim of the study is to present the case report of a patient with BWS, who was at the highest molecular risk of developing embryonal tumour associated with this syndrome. The authors emphasise the importance of therapy individualisation in BWS due to variable cancer predispositions associated with molecular aetiology.